Epileptic seizure prediction using relative spectral power features. Issue 2 (February 2015) - Bandarabadi, Mojtaba; Teixeira, César A.; Rasekhi, Jalil; Dourado, António
Highlights The proposed relative spectral power features resulted in an improved performance for seizure prediction. The number of selected features was 9.9 in average showing the efficiency of the introduced relative bivariate features. In average 75.8% of the test seizures (out-of-sample) were predicted across 1537 h of data with an average FPR of 0.1 h−1.